Análise da sustentabilidade dos sistemas construtivos da produção de habitação de interesse social - Ferrão, Marina Souza (Universidade Federal de São Carlos, 2021)
Sustainability is a concept that involves the tripod of economy, environment and social part. Its application in construction is increasingly present, encompassing the use of innovative materials, methods and systems. The use of sustainable construction has a direct impact on the well-being of residents and their quality of life. In Brazil, Housing of Social Interest (HIS) constantly seeks a lower production cost, executing projects with reduced spaces and low optimization. It is extremely important to involve sustainability in the housing of the low-income population who live in these HIS. This work aims to metrify the sustainability aspects in the construction systems used in the production of Social Interest Housing, having as object of study the HIS produced by CDHU in the state of São Paulo in the last decades. Through a survey of the types of construction systems used in the HIS, two samples of housing projects at CDHU were selected: Guaianazes A and Guaianazes B, with masonry sealing construction systems in ceramic blocks and in concrete blocks, respectively. Starting at information on the materials, equipment and labor used in these constructions, the MATSUS methodology tool was applied, where the sum of gas emission to the environment, solid waste production, energy and water consumption, financial cost, incentive to the local economy, social impacts, technical and performance impacts on recycling and reuse, physical-mechanical performance, technical reliability and ease of transport, storage and maintenance for the production of the construction systems analyzed. As a result, a greater sustainable efficiency of the masonry construction system of ceramic blocks was obtained in terms of environmental, economic and technical performance indicators. In the global assessment of sustainability, the construction system of masonry in ceramic blocks had the result of 52.69% against 47.31% of the system of masonry in concrete blocks in the metric and sustainable efficiency considering environmental, economic, social and technical performance aspects.
Analysis of the sustainability of constructive systems for production of social interest housing
Keywords: Sustentabilidade; MATSUS; Sistema construtivo; Habitação de interesse social; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL